Study of Sustainable Landscape Criteria in Order to Green Open Space Planning for Settlements in RW 9 Kelurahan Merjosari - Malang - Hamka Hamka; Sri Winarni; Adhi Widyarthara (ESE International Journal (Environmental Science and Engineering), 2020)
The green space in urban areas is the problem of its own for the speedy development. However, in our neighbourhood housing complex of RW 9 Joyogrand Merjosari village has potential housing facilities of empty land that could be used as green, active and productive space. The purpose of the study is to find the conceptual recommendation which relates to the development of sustainable green space benefiting the citizens and the natural environment. The methodology used is through study literature in accordance with green open space planning and sustainable landscape that includes 5 criteria; environment, economic, social and culture, an architectural aesthetic, institutional and, then conduct direct studies based on the criteria in question. Having conducted the survey, there was a space commensurate, open space for park, an open space for path and open space the island, but those potential spaces haven’t been properly used. Therefore, recommendations of sustainable green space development planning based on the sustainable landscape criteria is needed. From the environmental criteria, the physical qualities need to be increased. The economy can be increased by production activities such as productive plant cultivation and thematic space tourism development. The architectural planning for the gardens and environmental landmark can give space and attractive place experience. It also involves all agencies or group social housing in our neighbourhood RW.9 Joyogrand Merjosari urban village.